Historical relevance of Vygotsky’s work: Its significance for a new approach to the problem of subjectivity in psychology - Rey, Fernando Luis Gonzalez (Outlines. Critical Practice Studies, 2009)
This paper discusses theoretical issues concerning Vygotsky’s work that have remained unaddressed in the dominant interpretations of his work, either in the former Soviet psychology or in the dominant Western interpretations. This paper builds on interpretations of Vygotsky’s concepts oriented by the unity of emotional and cognitive processes and focused on the search for new psychical unities on which to build a systemic representation of the human mind. Because Vygotsky did not provide a definite position on such questions, I have centered on the analysis of the consequences of his legacy for the development of a definition of subjectivity from a cultural-historical standpoint.